Pengaruh Pengetahuan, Sosialisasi, dan Peran Relawan Pajak Terhadap Kepatuhan Pelaporan SPT TahunanWajib Pajak Orang Pribadi Karyawanpada KPP Pratama Sukoharjo - Faridha Nur Istiqomah; Fadjar Harimurti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of knowledge, socialization, and the role of tax volunteers on annual tax return compliance among individual employee taxpayers at the Sukoharjo Pratama Tax Office. The data used includes primary data obtained through questionnaires. The sample within this research comprised 110 participants, calculated using the Slovin formula with a purposive sampling method. To process the data, multiple linear regression processed within the SPSS program. The findings, Evidence form this research indicate that tax knowledge has no significant effect, while tax socialization and the role of tax volunteers significantly influence annual tax return compliance among individual employee taxpayers. This finding indicates that the active involvement of tax authorities through socialization and technical assistance by tax volunteers is a key determinant factor in encouraging tax compliance, considering that theoretical understanding alone is not strong enough to mitigate the procedural obstacles faced by taxpayers in fulfilling their tax obligation